PERADILAN AGAMA DALAM LINTASAN SEJARAH INDONESIA (SEBUAH PERTARUNGAN MEMPERTEGAS EKSISTENSI - M. Amin Nasution (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2024)
Islamic Court in Indonesia had undergone an up and down historical journey. At the very beginning, the Islamic Court which was well known as Priesterraden, was positioned as the second class court; compare to the state court (Landraad). Under colonial Dutch Government administration, eventhough Islamic court became a living court in moslem community, in fact through an unfair theory initiated by Christiaan Snouck Hurgronje, well known as Receptie Theory, the existence of Islamic court was examined. Later on, this theory had limited Islamic court’s realm (Absolute Competence) into private cases consisted of family law such as marriage, alms, taxes and a little bit inheritance. This situation was not changed under the Japanese administration. The significant change had happened in 1989 when the Indonesia government enacted the Law 7 year 1989 on Islamic Court in Indonesia. As time goes by, the Islamic Court in Indonesia has been improving its institution to a better situation more each time; specifically after the enactment of Law 35 Year 1999 on Integrated Judicial System. Recently, through the Law 3 Year 2006 on New edition of Islamic Court in Indonesia, the Islamic court’s realm was exceeded into Shari’ah economic cases. This reality had proved that moslem community believed in Islamic court performance to deal with their cases.